2018
DOI: 10.1093/annweh/wxy034
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety Education in Auto Body Collision and Machine Tool Technology Programs in Vocational Colleges: Challenges and Opportunities

Abstract: Collision repair, machining, and metal manufacturing are industries with a large percentage of small businesses whose owners face unique challenges implementing health and safety regulatory requirements. Previous research found that 72% of collision repair technicians and 47% of machinists attended some classes or graduated from vocational colleges. Although health and safety is a mandatory part of the curricula for post-secondary vocational education, little is known about what, how, and when health and safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This paper presents findings from group interviews with ABCT and MTT faculty at colleges participating in the TECHS program. Additional discussion and review of finding is found in Bejan et al…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This paper presents findings from group interviews with ABCT and MTT faculty at colleges participating in the TECHS program. Additional discussion and review of finding is found in Bejan et al…”
Section: Introductionmentioning
confidence: 91%
“…Faculty skilled in their technical area may lack knowledge related to health and safety and pedagogy. This knowledge gap is compounded by a deficiency or absence of high‐quality safety and health resources for vocational and technical college faculty, the use of outdated and often inaccurate information, and lack of any standardized assessment of knowledge and skills …”
Section: Introductionmentioning
confidence: 99%
“…Four papers focus on OS&H approaches for specific industries, the first being auto body collision and machine tool technology education (Bejan et al, 2018) and the others focused on the construction industry (Ringen et al, 2018; Cunningham et al, 2018; Marín and Roelofs, 2018). The focus of the work by Bejan and colleagues was to document how OS&H is taught and assessed over the course of a two-year vocational college program in auto body collision.…”
Section: Overview Of Papersmentioning
confidence: 99%
“…The focus of the work by Bejan and colleagues was to document how OS&H is taught and assessed over the course of a two-year vocational college program in auto body collision. They identified gaps and made recommendations for future training, which included providing trade-specific OS&H information, coaching, and support (Bejan et al, 2018). Ringen and colleagues provide an overview of the construction industry that describes trends over that past decade related to the 2008–2010 recession, followed by the recovery period.…”
Section: Overview Of Papersmentioning
confidence: 99%